Adattamenti e rielaborazioni nel passaggio di codice: dall’immagine ai versi. Il martirio di Maria Stuarda nel Poema heroico di Bassiano Gatti - Veronica Carta (Between, 2012)
The tragic history of Mary Stuart has been a true artistic inspiration for centuries. In 1633 the Gerolamin Bassiano Gatti published in Bologna the heroic poem Maria Regina di Scozia, recounting the history of her adventurous life and tragic death in the background of the Controriformistic fight against Anglicanism. An engraving depicting the scene of her cruel execution comes before the text. This essay analyzes the differences between the literary and the iconographic codes, highlighting  the author's and the engraver's different interpretations of the event.